2000
DOI: 10.1179/joc.2000.12.4.352
|View full text |Cite
|
Sign up to set email alerts
|

Potential Transmission of the Cytogenetic Effects of Cisplatin in the Male Germline Cells of Swiss Mice

Abstract: Cisplatin (CP) (in Oncoplatin), a widely used drug in cancer chemotherapy, and cyclophosphamide (CY) (in Endoxan), another anticancer drug, were investigated as the test chemical and positive control, respectively, for their cytogenetic effects on spermatogonia of mice at 24 hours post-treatment after a single exposure. The different doses of the chemicals tested were CP 2, 3, 5 mg/kg and CY 40 mg/kg b.w. of mice. Each of the doses of CP induced a significant number of chromosomal aberrations, mostly chromatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Induction of sex-linked recessive lethal mutation in male germ cells (Woodruf et al 1980) and clastogenicity in spermatocytes and spermatogonia (Brodberg et al 1983) in Drosophila melanogaster by cisplatin have been reported. Cisplatin induced significant aberrant spermatocytes, autosomal and sex chromosomal univalents, tetravalents etc., in male mice (Adler and el-Tarras 1990;Choudhury et al 2000). Platinum compounds also reduced the sperm motility in humans (Kesseru and Leon 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of sex-linked recessive lethal mutation in male germ cells (Woodruf et al 1980) and clastogenicity in spermatocytes and spermatogonia (Brodberg et al 1983) in Drosophila melanogaster by cisplatin have been reported. Cisplatin induced significant aberrant spermatocytes, autosomal and sex chromosomal univalents, tetravalents etc., in male mice (Adler and el-Tarras 1990;Choudhury et al 2000). Platinum compounds also reduced the sperm motility in humans (Kesseru and Leon 1974).…”
Section: Discussionmentioning
confidence: 99%
“…In studies in male mice, cisplatin induced chromosomal aberrations in spermatocytes, as well as differentiating spermatogonia immediately after the treatment. However, long after exposure, the transmission of such effects was found to have decreased substantially by the time the exposed spermatogonia matured [68].…”
Section: Cisplatin and Analogsmentioning
confidence: 98%
“…Cisplatin causes DNA cross-linking, an effect that inhibits DNA repair and synthesis, particularly in neoplastic cells. 48 Etoposide interferes with the transcription and replication of DNA which is followed by a cytotoxic effect. Bleomycin is an antibiotic agent capable of disrupting DNA chains in cancer cells.…”
Section: Chemotherapymentioning
confidence: 99%